2012
DOI: 10.1111/j.1365-2419.2012.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of temperature, bathymetry and fronts on spawning migration routes of Icelandic capelin (Mallotus villosus)

Abstract: Capelin (Mallotus villosus) is the largest commercial fish stock in Icelandic waters and also an important forage fish. Capelin have adapted to the sub‐arctic environment by migrating north (67–72°N) to feed during summer in deep cold waters (>500 m; 1–3°C) before migrating south (63–65°N) to spawn in winter in warm shallow waters on the south and west coasts of Iceland (<100 m; 5–7°C). Hydroacoustic data on capelin spawning migrations from 1992 to 2007 revealed a consistent southward route along which capelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Usually, the pelagic prey of cod form aggregations that have dimensions that are orders of magnitude larger in the horizontal than vertical plane (Ressler et al 2005, Olafsdottir & Rose 2012. Therefore, vertical searching may be an important strategy in locating these prey patches.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the pelagic prey of cod form aggregations that have dimensions that are orders of magnitude larger in the horizontal than vertical plane (Ressler et al 2005, Olafsdottir & Rose 2012. Therefore, vertical searching may be an important strategy in locating these prey patches.…”
Section: Discussionmentioning
confidence: 99%
“…Interannual variability in the spatial distribution of the landings (inferred from VMS signals) suggests that additional factors may have been influencing fishing activity. For instance, previous research has indicated that changes in sea temperature, currents, subsurface upwelling and attendant food availability (associated not only with seasonal and interannual variability, but also with less predictable events such as storms and turbidity currents) can influence the migratory routes of deep sea fish and their choice of location for gonad development and spawning activity (Overholtz et al 2011;Crawford et al 2012;Jury 2012;Olafsdottir and Rose 2012). The variability is often reflected in the spatial distribution of fishing activity, as captured in Figure 4; in general, annual fluctuations in the regions of greatest intensity tend to travel back and forth along the depth contours of the continental slope.…”
Section: Discussionmentioning
confidence: 99%
“…Capelin ( Mallotus villosus ) are a small (12–20 cm at maturity) schooling pelagic fish with circumpolar distribution (Vilhjálmsson, ). In Icelandic waters, capelin undertake an annual spawning migration each winter that covers 500–1000 km from northern summer feeding areas in the Iceland Sea (67–71°N; Vilhjálmsson, ) to coastal spawning waters (<200 m bottom depth) south and west of Iceland (Vilhjálmsson, ; Olafsdottir and Rose, ). This migration has been researched annually since the late 1970s because of its commercial and biological importance (Vilhjálmsson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, capelin migrate inshore to spawn. Early phases of the migration appear to vary temporarily, with the leading edge of the migration reported to reach latitude 64°N at variable times during January (Vilhjálmsson, ; Olafsdottir and Rose, ). However, such temporal variability in the early phases of migration does not appear to influence the timing of the final phase of the migration onto the continental shelf, as capelin have never been located in inshore waters before February.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation